TANGGUNG JAWAB BRI ATAS HILANGNYA DANA SIMPANAN NASABAH BERDASARKAN PERATURAN PERBANKAN - Jami Allaidin; Suci Lestari (Reformasi Hukum Trisakti, 2021)
According to Decision Number 211/Pid.sus/2020/PN.Jmb, BRI employee Tumbi Partimbo Pati, who worked as a representative in Abunjani Sipin, Jambi City, defrauded BRI consumers. The phrasing of the issue is whether the decision has applied BRI's responsibility towards consumers based on banking regulations and if BRI's notion of liability for fraud is based on bank secrecy requirements and the Financial Services Authority. The research approach is normative, descriptive in character, uses secondary data, analyzes qualitative data, and relies on deductive reasoning to reach findings. According to the study's findings, analysis, and conclusion, BRI's notion of responsibility for fraud is based on rules governing bank secrecy and the Financial Services Authority, and the bank is not liable for client losses brought on by negligence by the customer himself not maintaining the secrecy of his ATM PIN but customers can request compensation from perpetrators who commit fraud. the fraud and implementation of BRI's responsibility verdict towards customers based on banking regulations, the bank is not criminally responsible but the person who committed the act is convicted, the bank bears the actions of its employees who commit fraud by giving administrative sanctions from the Financial Services Authority based article 52 the Banking Law.